How to build a digital library - Witten, I. H. (Ian H.); Bainbridge, David, 1969- (Amsterdam ; London : Morgan Kaufmann, 2002)
Given modern society's need to control its ever-increasing body of information, digital libraries will be among the most important and influential institutions of this century. With their versatility, accessibility, and economy, these focused collections of everything digital are fast becoming the "banks" in which the world's wealth of information is stored. How to Build a Digital Library is the only book that offers all the knowledge and tools needed to construct and maintain a digital library-no matter how large or small. Two internationally recognized experts provide a fully developed, step-by-step method, as well as the software that makes it all possible. How to Build a Digital Library is the perfectly self-contained resource for individuals, agencies, and institutions wishing to put this powerful tool to work in their burgeoning information treasuries. * Sketches the history of libraries-both traditional and digital-and their impact on present practices and future directions * Offers in-depth coverage of today's practical standards used to represent and store information digitally * Uses Greenstone, freely accessible open-source software-available with interfaces in the world's major languages (including Spanish, Chinese, and Arabic) * Written for both technical and non-technical audiences * Web-enhanced with software documentation, color illustrations, full-text index, source code, and more.
Orientation : the world of digital libraries -- Preliminaries : sorting out the ingredients -- Presentation : user interfaces -- Documents : the raw material -- Markup and metadata : elements of organization -- Construction : building collections with Greenstone -- Delivery : how Greenstone works -- Visions : future, past, and present.
Includes bibliographical references and index.
Keywords: Digital libraries; Electronic books